Challenge for Cause - Phillips, Lord Justice (Victoria University of Wellington Law Review, 1996)
In this article, his Lordship examines the operation of juries in England and considers how the English experience may assist the New Zealand Law Commission in the reform process. His Lordship addresses three aspects: first, the implications of jury operation and selection processes; second, the role of the law of evidence in determining the guilt or innocence of an accused; third, whether juries are the appropriate finder of fact in trials concerning serious fraud. The material in this article was originally delivered as a public lecture on 27 March 1996 in the Faculty of Law.